Carbon Nanotubes in Portland cement concrete: Influence of dispersion on mechanical properties and water absorption - Marcondes, C. G. N.; Medeiros, M. H. F.; Marques Filho, J.; Helene, P. (Revista ALCONPAT, 2015)
Carbon nanotubes (CNTs) are carbon structures that take the shape of cylinders in nanometric scale. Thispaper presents an evaluation about addition of CNTs in Portland cement concrete, focused in theimportance of performing the CNTs dispersion in water using ultrasound before its incorporation to theconcrete mass. For that, three concrete mixtures were prepared, one without CNT (reference series) andtwo with CNTs (one mixture with previous dispersion in water and additive using ultrasound and theother without dispersion). Then properties of fluidity, compressive and tensile strength and waterabsorption were analyzed. The amount of CNT added was 0.30% with respect to cement mass. In allcases, the previous dispersion of CNTs using ultrasound potentiated the effect of CNTs addition,demonstrating to be important for the efficiency of this material when added to cement.Keywords: carbon nanotubes; concrete; strength; water absorption.